Community Engagement, Heritage, And Rediscovering A Sense Of Place In Northbridge, Perth, Australia - EdnieBrown, Felicity Morel (Penerbit Universiti Sains Malaysia (USM Press), 2011)
This paper explores the richness that has been discovered in Western Australia's capital city, Perth, through the Northbridge History Project (NHP)—a five year initiative whose role was to revitalise the city authentically by drawing on its diverse histories. Containing sites of recognised cultural heritage significance, Northbridge in Western Australia has undergone significant infrastructural and generational change in the last twenty years, bringing with it dislocation of its identity. Discovering and making available the histories of this diverse area in an Electronic Archive (EA) has created a new sense of identity and community engagement, bringing awareness that the area's living cultural heritage is valuable and has much to offer the city as it seeks to position itself as Australia's Indian Ocean gateway.